HACKER DALAM PERSPEKTIF HUKUM INDONESIA - Bambang Hartono (Masalah-Masalah Hukum, 2014)
Hackeris a Cyber Crimes, often occurbut untilnowthere has been nolegalbasis of the mostpowerful tohandlethe cases, eventhe development of cybercrime in the world is getting fierce. In addition to using advanced tools, modes of cybercrime is also quiteneat. Thisis so great crimes can bedevastating even internationally. Cybercrime is quite complicated dynamics. Therefore, do notrecognizenational boundariesand regions. In addition, the time the crime was difficult to determine. Cyber? Crime is a phenomenonfullrankcandidatesforthe biggestcrimein the future